Evaluation of Antibiotic Use in the Internal Medicine Ward and ICU at Universitas Tanjungpura Hospital Pontianak with ATC/DDD - Rifdah, Dzuria Adhana; Ih, Hariyanto; Liana, Delima Fajar; Mardhia, Mardhia; Mahyarudin, Mahyarudin (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Background: Evaluating the wise use of antibiotics is needed to control antibiotic resistance in hospitals.Objectives: This study aimed to analyze patient characteristics, antibiotic profiles, and quantitative use of antibiotics in inpatients prescribed by internal medicine specialists in the internal medicine ward and Intensive Care Unit (ICU) at Universitas Tanjungpura Hospital Pontianak from August to October 2022.Methods: This study method is descriptive observational, and data collection was done retrospectively using a purposive sampling technique. There were 143 samples that met the inclusion criteria, and then using the Anatomical Therapeutic Chemical (ATC)/Defined Daily Dose (DDD) method, the samples were analyzed quantitatively.Results: Most patient characteristics were female patients (60.14%), patients aged 56-65 (26.57%), and the most common diagnosis was typhoid fever (32.74%). Of the 13 types of antibiotics used, cephalosporin was the most commonly prescribed antibiotic group to patients (58.48%), with the most types of antibiotics in ceftriaxone (42,69%) and intravenous administration of antibiotics was the standard route given to patients. The results of the quantitative analysis of all antibiotic prescriptions obtained a total value of 88.55 DDD/100 patient-days. Antibiotics with the most considerable DDD/100 patient-days value were ceftriaxone (44.71), followed by meropenem (10.46) and levofloxacin (9.28). Furthermore, the value of DDD/100 patient-days is not an indicator in determining the rational use of antibiotics, so further study must be done using the Gyssens method.Conclusion: The value of DDD/100 patient-days is not an indicator in determining the rational use of antibiotics, so further study must be done using the Gyssens method as qualitative evaluation to obtain information regarding the rationality of prescribing antibiotics.